Filsafat Ishrāqiyyah (Iluminatif) Suhrawardī al-Maqtūl - Ahmad Hasan Ridwan (Al-Jami'ah Research Centre, 1998)
The Ishrāqī is oriental as well as illuminative philosophy. It is to shine, for it comes from the Orient; and it is oriental, because it shines. Colored with its distinct language, this philosophy constitutes an alliance between the